Information and communication technology adoption and staff performance in public tertiary institutions in Bauchi State, Nigeria - Abdullahi, Aliyu Dahuwa (2019)
The global outcry for administrative efficiency in the context of public affairs necessitated some organizations in the Nigerian public sectors to adopt technology as an instrument for effective and efficient service delivery. This study, therefore, investigated the influence of technological attributes on the perception of administrative staff to adopt information and communication technology facilities in their primary responsibilities for effective performance in Bauchi state public tertiary institutions. Data were collected using questionnaires and semi-structured interview questions. After preliminary data screening using SPSS, 382 questionnaires were used in quantitative data analysis, while 8 respondents were interviewed. The respondents were selected from six tertiary institutions in Bauchi state due to its peculiarity with the issue. PLS-SEM was used to analyse the responses generated from the questionnaires while NVIVO was used to analyse the interviews transcribed data using a thematic approach. The study was conducted using a convergent parallel designed of quantitative and qualitative approach. The quantitative approach consists of 16 hypotheses, out of which 12 were supported, while 4 were not supported. The findings of this study demonstrated the significance of the adopted variables as capable of influencing the rational decision of non-teaching staff to improve their performance through actual use of technological attributes. However, the study observed some limitations with regard to the ICT facilities in achieving the needed performance without the fundamental administrative structures as identified in the qualitative analysis. The Implications of the finding are discussed in relation to the theoretical, practical, and methodological postulations. The study contributes to the theory and practice of, information system, public policy, and administration, as well as provides policymakers and top management staff with the understanding of ICT adoption as a panacea to poor staff performance, in public tertiary institutions.